1998
DOI: 10.1182/blood.v91.6.2076.2076_2076_2084
|View full text |Cite
|
Sign up to set email alerts
|

ALK-Positive Lymphoma: A Single Disease With a Broad Spectrum of Morphology

Abstract: The t(2;5)(p23;q35) translocation, associated with anaplastic large-cell lymphoma (ALCL), results in the expression of a chimeric NPM-ALK protein that can be detected by the ALK1 monoclonal antibody. This report describes the morphologic and phenotypic spectrum of 123 cases of lymphoma that all express ALK protein. The results provide strong evidence that the morphologic patterns of ALCL described in previous reports as representing possible subtypes of ALCL, eg, common type, lymphohistiocytic, or small cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
84
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(97 citation statements)
references
References 33 publications
10
84
0
3
Order By: Relevance
“…Comparison of the molecular analyses with the immunohistochemical ALK staining pattern revealed complete concordance: all NPM1-ALK positive ALCL expressed ALK in the nucleus while no tumour with a variant ALK fusion transcript showed nuclear ALKstaining. This first molecular-immunohistological correlation in a large cohort of children with ALCL substantiates earlier descriptions from case series (Benharroch et al, 1998;Falini et al, 1999;Perkins et al, 2005).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Comparison of the molecular analyses with the immunohistochemical ALK staining pattern revealed complete concordance: all NPM1-ALK positive ALCL expressed ALK in the nucleus while no tumour with a variant ALK fusion transcript showed nuclear ALKstaining. This first molecular-immunohistological correlation in a large cohort of children with ALCL substantiates earlier descriptions from case series (Benharroch et al, 1998;Falini et al, 1999;Perkins et al, 2005).…”
Section: Resultssupporting
confidence: 87%
“…This is in line with the results of a smaller study of Perkins et al, (2005), which identified 3/34 (9%) variant fusions by FISH and 4/42 (9AE5%) by ALK cytoplasmic staining. The proportion of the variant ALK-fusion partners seems to be lower in children (£10%) compared to adults (20-25%) according to studies that relied on the ALK staining pattern in adults (Benharroch et al, 1998;Falini et al, 1999). One earlier case series suggested a higher proportion of variant ALK fusion genes among children with ALCL defined by aberrant karyotypes (Liang et al, 2004 ALK-positive ALCL and was hampered by a low concordance between cytogenetics, FISH and ALK-staining pattern.…”
Section: Resultsmentioning
confidence: 99%
“…Morphologically, ALK-positive ALCL has several variants, which may mimic Hodgkin lymphoma, a sarcoma, or an inflammatory process [1,1418]. Common to all is the presence of cells with eccentric reniform nuclei and an eosinophilic or pale paranuclear hof known as “hallmark cells.” When there is only partial involvement of a lymph node, the cells may grow in a sinusoidal distribution or colonize the paracortex in a cohesive manner and may mimic metastatic carcinoma or other anaplastic epithelioid malignancies [11].…”
Section: Discussionmentioning
confidence: 99%
“…A T-cell antigenic phenotype was reported in slightly more than half of the ALCLs; the remaining cases had a null phenotype [22]. However, with a more extensive immunohistochemical study including multiple-surface T-cell antigens (CD2, CD3, CD4, CD5, CD7, CD8, CD43, CD45RO, LAT), we have demonstrated a T-cell phenotype in as many as 88% of the cases.…”
Section: Discussionmentioning
confidence: 61%